IMPACT OF REFLEXOLOGY ON MECHANICAL LOW BACK PAIN (International Journal of Physiotherapy, 2015)
Background: Low-back pain (LBP) is one of the highest common and costly musculoskeletal conditions in current society. Seventy to 85% of the populations will exhibits LBP at some time in their lives. There is little known about specific manual therapy techniques used to treat chronic LBP. Reflexology is a treatment that involves using gentle pressure to reflex points located on all of the outsides of the feet and hands. The aim of the study was to investigate the efficacy of reflexology technique in subjects with chronic low back pain (CLBP).Methods: Twenty patients with nonspecific chronic low back pain were included in the study and were assessed regarding range of motion via goniometer and pain threshold (via modified Oswestery scale and visual analogue scale), the 20 patients were allocated into two groups 10 patients in each group. Group A received reflexology sittings at rate of 3 days per week, and the duration of each sitting was 30 minutes. While group B were control. The study was continued for 3 weeksResults: According to VAS, the results revealed a non-significant variance between the study group and control group before intervention (p= 0.43). While after intervention, there was a significant decline of pain in the study group compared to that of the control group (p=0.000). Moreover, there was a very highly significant decrease in pain within the study group after treatment (p= 0.005).Conclusion: The present study indicated that the reflexology technique was effective and safe to be applied for cases of mechanical low back pain. It results in a significant decrease in pain within the study group after treatment.